Characterization of Frechet spaces with nuclear Kothe quotients - Sah, Satya Narayan (BIBECHANA, 2014)
In this paper our result based on the characterization of Frechet spaces with nuclear Kothe quotients is in terms of the following condition which labeled as ?. We show that a Frechet spaces E satisfies condition ? if and only if it has a quotient which admits continuous norm and satisfies condition ?. For the condition ?, there exists ? such that for every k there exists j such that the ?. ?kclosure of E′? is not closed in E′j. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10397 BIBECHANA 11(1) (2014) 161-164